2015
DOI: 10.14238/pi55.3.2015.171-5
|View full text |Cite
|
Sign up to set email alerts
|

Reticulocyte hemoglobin content as a predictor of iron deficiency anemia

Abstract: Background Iron deficiency anemia (IDA) is the most common

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 3 publications
0
4
0
4
Order By: Relevance
“…Salah satu pemeriksaan spesifik untuk menilai defisiensi besi yang direkomendasikan American Academy of Pediatrics (AAP) adalah reticulocyte hemoglobin equivalent (Ret-He) atau reticulocyte hemoglobin content (CHr). 13,20 Perbedaannya, CHr dianalisis dengan alat ADVIA 120 dan 2120, sedangkan Ret-He dianalisis dengan XE 2100, XE 5000 dan seri XN; keduanya menunjukkan korelasi yang baik. [21][22][23] Ketersediaan besi fungsional untuk dimasukkan ke dalam eritrosit dalam sumsum tulang selama eritropoiesis tercermin dari jumlah Hb dalam retikulosit, sehingga Ret-He menunjukkan kecukupan zat besi dalam sumsum tulang untuk eritropoiesis.…”
Section: Peran Ret�he Sebagai Parameter Defisiensi Besiunclassified
“…Salah satu pemeriksaan spesifik untuk menilai defisiensi besi yang direkomendasikan American Academy of Pediatrics (AAP) adalah reticulocyte hemoglobin equivalent (Ret-He) atau reticulocyte hemoglobin content (CHr). 13,20 Perbedaannya, CHr dianalisis dengan alat ADVIA 120 dan 2120, sedangkan Ret-He dianalisis dengan XE 2100, XE 5000 dan seri XN; keduanya menunjukkan korelasi yang baik. [21][22][23] Ketersediaan besi fungsional untuk dimasukkan ke dalam eritrosit dalam sumsum tulang selama eritropoiesis tercermin dari jumlah Hb dalam retikulosit, sehingga Ret-He menunjukkan kecukupan zat besi dalam sumsum tulang untuk eritropoiesis.…”
Section: Peran Ret�he Sebagai Parameter Defisiensi Besiunclassified
“…Some studies show that Ret-He is excellent for detecting iron deficiency [18,[24][25][26][27]]. Suari's study to detect IDA with a Ret-He cut-off value of 23.1 pg at the age of 6-60 months had a sensitivity of 88%, specificity of 25%, the positive predictive value of 34%, and a negative predictive value of 82% [14]. The Lorenz study to detect iron deficiency with a Ret-He cut-off value of 29 pg in corrected infants aged 3-4 months (<32 weeks and <1500 grams) had a sensitivity of 85%, specificity 73%, positive predictive value 33%, and a negative predictive value of 97% [21].…”
Section: P R E P R I N Tmentioning
confidence: 99%
“…The diagnostic power of Ret-He for detecting iron deficiency without anemia is higher than serum ferritin and Hb (sensitivity 70-94%, specificity 72-80%) [17], and superior to ferritin or zinc protoporphyrin/heme ratio in neonates [31]. Several studies of Ret-He to detect iron deficiency in infants showed a sensitivity of 70-94%, specificity 72-80%, positive predictive value 33-34%, and negative predictive value 82-97% [14,17,21].…”
Section: P R E P R I N Tmentioning
confidence: 99%
See 2 more Smart Citations